A Study of Muslim Philosophersâ Views about Rhythm and Rhyme (with emphasis on the works of Aristotle, al-Farabi, Averroes, Ibn Sina, Baghdadi, Khajeh Nasir and Ghartajeni) - S. Mahdi Zarghani (Literary Arts, 2013)
Â Abstract